2002
DOI: 10.1002/etc.5620210117
|View full text |Cite
|
Sign up to set email alerts
|

Aminolevulinic acid dehydratase activity in American dippers (Cinclus mexicanus) from a metal‐impacted stream

Abstract: Blood samples collected from adult and nestling American dippers (Cinclus mexicanus) along the Arkansas River (CO, USA), a stream impacted by discharges from historical mining operations, and a reference stream were analyzed for lead concentration and delta-aminolevulinic acid dehydratase (ALAD) activity. Median ALAD activities of adult and nestling dippers from the Arkansas River were found to be significantly different from median ALAD activities of reference adults and nestlings (p = 0.002 and p = 0.028). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…, 1996; Sorace et al. , 2002) and North America (Strom et al. , 2002; Feck & Hall, 2004; Henny et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1996; Sorace et al. , 2002) and North America (Strom et al. , 2002; Feck & Hall, 2004; Henny et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these effects on dippers are so well defined that they have been widely proposed as indicator species in the monitoring and management of lotic systems (Sorace et al. , 2002; Strom, Ramsdell & Archuleta, 2002; Feck & Hall, 2004). However, such studies on the population dynamics and distribution of dippers rarely consider the effect of flooding (but see Price & Bock, 1983), which can be a major disturbance in river systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, predators feeding on metal‐ contaminated biota, including the dipper, are at risk for elevated exposure from its aquatic diet. Strom et al [8] confirmed adult and nestling American dippers were exposed to lead through their invertebrate prey in a mine‐impacted river system. Therefore, dippers can be an effective model for monitoring metal pollution in mountain streams because they integrate contaminant sources from their aquatic diet over time and space.…”
Section: Introductionmentioning
confidence: 99%
“…The aquatic songbird American dipper Cinclus mexicanus (American Ornithologists’ Union 1998) occupies mountainous watersheds year‐round and has proven useful as a biomonitor of metal pollution (Strom, Ramsdell & Archuleta 2002). The Eurasian dipper Cinclus cinclus L. has also been shown to be a useful indicator of organochlorine (OC), polychlorinated biphenyl (PCB) and mercury (Hg) pollution in upland river catchments (Ormerod & Tyler 1990, 1992; O’Halloran et al .…”
Section: Introductionmentioning
confidence: 99%